DEVELOPING LEARNING PATTERN IN BUSINESS WITH K-SMART MODEL TO PROMOTE ENTREPRENEURSHIP COMPETENCE ON PRATOMSUKSA SIX LEVEL STUDENTS AT BANHAIMAIPAN SCHOOL - Nurangsee, Yanin (Journal of MCU Nakhondhat, 2025)
This research aimed to: 1) Study the problems, needs, and guidelines for developing a learning model to promote entrepreneurship abilities for grade 6 students at Banhuaimaipan School; and 2) Develop a business learning model based on the "6 Knowledge" concept to enhance entrepreneurship abilities for grade 6 students at Banhuaimaipan School. The research employed a Research and Development methodology divided into 2 phases. Phase 1: The informants consisted of administrators, teachers, and parents at Banhuaimaipan School, totaling 56 participants selected through purposive sampling. The research instrument was a questionnaire with a reliability of 0.741. Phase 2: The informants included teachers, educational supervisors, and experts in entrepreneurship, totaling 5 participants selected through purposive sampling. The research instruments included a document analysis form, small group meeting record form, and evaluation form with a reliability of 0.831. Data were analyzed using frequency, percentage, mean, standard deviation, and content analysis. The findings revealed that: 1) Teachers lacked instructional approaches to promote entrepreneurship abilities, lacked creativity in learning management, had insufficient integration of entrepreneurship skills with content, and had limited budget support. Development needs for learning included market outlets for products, hands-on experience for students, budget support, business knowledge development, and promotion of integrity. Guidelines for developing the learning model showed that the model comprised 5 components: principles, objectives, learning process, organizational system, and measurement and evaluation. Entrepreneurship abilities consisted of 5 aspects: Creativity, determination and commitment, self-confidence, business knowledge, and business ethics; and 2) The business learning model based on the "6 Knowledge" concept demonstrated appropriateness at the highest level.